Republic of Armenia : Request for Arrangement Under the Extended Fund Facility. (IMF Staff Country Reports; Country Report, 2014)
This paper discusses Armenia's Request for Arrangement Under the Extended Fund Facility (EFF). Performance under the 2010-2013 program, which was supported by arrangements under the EFF and Extended Credit Facility (ECF), was sound, with growth restored, large fiscal and external imbalances reduced, and buffers rebuilt. However, challenges remain, particularly in further reducing vulnerabilities and strengthening medium-term growth dynamics. Fiscal policy will support the growth recovery in 2014 by providing a modest stimulus, before moving to a gradual consolidation stance in 2015-2017. The IMF Staff supports the authorities' request for an IMF-supported program.